Adult–onset Type 1 Diabetes Mellitus Patients Treated Successfully with Insulin and Continuous Glucose Monitoring (CGM): Autoimmunity and CGM in Focus - A. Manov; S. Chauhan; G.Dhillon; A. Donepudi (Achievements and Challenges of Medicine and Medical Science Vol. 12, 2025)
Type 1 Diabetes Mellitus (DM) in adults is currently more common than in children, as traditionally thought. The new data show that up to 40% of Type 1 DM in adults above the age of 30 is misdiagnosed as type 2 DM. The reason for this is that Type 1 DM in adults has a slightly different clinical presentation, usually is not as acute as in children, and can have a short period in which insulin is not needed, generally less than 6- months compared to Latent autoimmune diabetes in adults (LADA). The other reason is that the physicians think that if DM is diagnosed above 40, the patients have DM type 2. This was the traditional way of thinking in the past. Also, 61% of patients with Type 1 DM are overweight and/or obese, which further makes the clinical diagnosis more difficult. In our case series we are describing two patients misdiagnosed for 14- years one of them and for 4- years the other one as having DM type 2. They were, from the beginning of their Disease treated with Insulin and other oral antidiabetic medications as well as injectable GLP1-RAG and had very brittle DM, admissions in the hospital for DKA’s, and inferior control of their disease. Both of them had DKA as the initial presentation of their DM. We saw those two patients in the clinic and proved that they have adult-onset type 1 DM by checking their GAD-65, IA-2, and Zn- T8 antibodies, which were very positive and showing that their C-peptide was undetectable while their plasma glucose was between 80-180 mg/dl. We treated them with a Basal bolus Insulin regimen and stopped other oral or injectable antidiabetic medications. We switched them from self-monitoring their blood Glucose (SMBG) four times a day to Continuous Glucose monitoring (CGM) with the devices Dexcom G6 and Dexcom G7. The patients were sharing their CGM data with our Internal Medicine Residency clinic. The Internal medicine Residents, part of the CGM team under the supervision of a Certified Endocrinologist who was a part of the clinic, were adjusting their Insulin bi-weekly and seeing the patients every two months. The control of their adult-onset DM type 1 improved significantly after the right diagnosis had been given and CGM introduced.